OP0049 The lenght of remission and rate of relapse after tocilizumab withdrawal in rheumatoid arthritis patients. (23rd January 2014) - Aguilar-Lozano, L.; Padilla-Ibarra, J.; Sandoval-Castro, C.; Castillo-Ortiz, J.D.; Morales-Torres, J.; Hernandez, C.; Burgos-Vargas, R.; Pacheco-Tena, C.; Ramos-Remus, C.
Abstract : Background: Although there is much discussion regarding when to initiate a biological agent in rheumatoid arthritis (RA) patients, data on when to stop these agents is scant. Disease activity outcomes after the ending of an industry sponsored clinical trials may provide useful information regarding the duration of drug-free remission for a given biological agent. Objectives: To assess the length of remission and rate of relapse of disease activity after ending the open label, long-term extension study (5 yrs) using tocilizumab in RA patients enrolled in the OPTION trial. Methods: Patients who no longer received tocilizumab because of the ending of the extension study (5 yrs) of the OPTION trial were analyzed. All patients were: a) in remission (DAS28 <2.6, 0 swollen joints) at the time of the last tocilizumab administration (week 260), b) followed thereafter every 8 weeks until relapse (1 or more swollen joints), c) on a stable methotrexate dose during the follow-up. Results: Forty patients were analyzed, 85% females with a mean age of 53.5 yrs. During the first 12 months of follow-up, 21 (52.5%) patients continued in remission. Relapses occurred in 19 (47.5%) patients, 11 (58%) of them during the first three months after the last tocilizumab administration. No variables were identified to predict length of remission. Conclusions: Long-term remission is possible in a substantial number of RA patients after suspension of tocilizumab. Additional data are required to support recommendations for discontinuing a biological agent after achieving remission. These recommendations would impact in patients' safety and the economic burden imposed by these treatments. References: Smolen JS, Beaulieu A, Rubbert-Roth A, Ramos-Remus C, Rovensky J, et al. Effect of interleukin-6 receptor inhibition with tocilizumab in patients with rheumatoid arthritis (OPTION study): a double-blind, placebo-controlled, randomised trial. Lancet 2008;371:989–97. Disclosure of Interest: None Declared